KHUSYU' DALAM AL-QUR'AN - Ahmad Zakki Mubarak (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
.1,. m8 ,rr oD's 'o d..uj, r_hF,obo, ofdevour ; ihF eu/,n wheD, -., ,- i , .r- ,o-.1ed (,r, ,n prflolfug rus relrgj*. *